Wittgenstein on thought and will - Teichmann, Roger, 1963- (Wittgenstein's thought and legacy, 2015)
This book examines in detail Ludwig Wittgenstein's ideas on thought, thinking, will and intention, as those ideas developed over his lifetime. It also puts his ideas into context by a comparison both with preceding thinkers and with subsequent ones. The first chapter gives an account of the historical and philosophical background, discussing such thinkers as Plato, Descartes, Berkeley, Frege and Russell. The final chapter looks at the legacy of, and reactions to, Wittgenstein. These two chapters frame the central three chapters, devoted to Wittgenstein's ideas on thought and will. Chapter 2 di.